COMUNITAR CENTRATE: 23 DE MOTIVE PENTRU CARE BIBLIOTECA TA ESTE LOCUL CEL MAI IMPORTANT DIN LOCALITATE (TRADUCERE DE LIDIA KULIKOVSKI) - Biando EDWARDS, Julie; S. RAUSEO, Melissa; Rae UNGER, Kelley (BIBLIOPOLIS, 2020)
This book is for those moving their library beyond places to find information. Written by practicing public librarians and an academic librarian with an interest in public libraries, the book focuses on how public libraries can become more community centered and, by doing so, how they can transform both themselves and their communities. The authors argue that focusing on building community through innovative and responsive services and programs will be the best way for the public library to reposition itself in the years to come. Repositioning the library acknowledges that information is in abundance in contemporary life. And while accessing information will always be at the heart of what libraries do, it isn t the only thing they do. The book looks at how community centered libraries build individual and community assets and how, in doing so, they serve as essential community anchors and institutions.